Can tobacco dependence provide insights into other drug addictions?. Issue 1 (December 2016) - DiFranza, Joseph
Abstract Within the field of addiction research, individuals tend to operate within silos of knowledge focused on specific drug classes. The discovery that tobacco dependence develops in a progression of stages and that the latency to the onset of withdrawal symptoms after the last use of tobacco changes over time have provided insights into how tobacco dependence develops that might be applied to the study of other drugs. As physical dependence on tobacco develops, it progresses through previously unrecognized clinical stages of wanting, craving and needing. The latency to withdrawal is a measure of the asymptomatic phase of withdrawal, extending from the last use of tobacco to the emergence of withdrawal symptoms. Symptomatic withdrawal is characterized by a wanting phase, a craving phase, and a needing phase. The intensity of the desire to smoke that is triggered by withdrawal correlates with brain activity in addiction circuits. With repeated tobacco use, the latency to withdrawal shrinks from as long as several weeks to as short as several minutes. The shortening of the asymptomatic phase of withdrawal drives an escalation of smoking, first in terms of the number of smoking days/month until daily smoking commences, then in terms of cigarettes smoked/day. The discoveries of the stages of physical dependence and the latency to withdrawal raises the question, does physical dependence develop in stages with other drugs? Is the latency to withdrawal for other substances measured in weeks at the onset of dependence? Does it shorten over time? The research methods that uncovered how tobacco dependence emerges might be fruitfully applied to the investigation of other addictions.